Transformasi Kebijakan Mutu Pendidikan Berbasis Teknologi: Mewujudkan Sistem Pendidikan Futuristik, Berkualitas, Tangguh, Dan Berkelanjutan Dalam Era Society 5.0 Di Perguruan Tinggi - Husnul, Nisak Ruwah Ibnatur (Universitas Tidar, 2025)
The transformation of technology-based quality assurance policies has become a strategic necessity for higher education institutions in the era of Society 5.0, where digital technology serves as a catalyst for enhancing national competitiveness and educational excellence. Universities are required not only to maintain administrative quality standards but also to develop adaptive, data-driven, and sustainable quality systems. This paper aims to analyze and synthesize contemporary theories relevant to formulating a conceptual model of technology-based quality policy in higher education. This study employs a qualitative method through a library research approach and conceptual analysis, conducted by critically examining theories of quality management, digital leadership, learning innovation, and recent educational policies (2020–2025). The synthesis reveals that the integration of Digital Quality Management (DQM), the Technology Acceptance Model (TAM), Technological Pedagogical Content Knowledge (TPACK), Learning Analytics, and Digital Leadership forms the core foundation for constructing a futuristic and outcome-oriented quality policy framework. Based on this analysis, a conceptual model titled the Digital Quality Policy Model for Higher Education in Society 5.0 (DQPM–HE5.0) is proposed, consisting of four key pillars: (1) Governance and Digital Leadership, (2) Digital Quality Management Systems, (3) Human Capacity and Pedagogical Innovation, and (4) Sustainability and Resilience. This model represents a dynamic quality policy system that emphasizes continuous improvement and is grounded in empirical data. Its implementation is expected to foster a smart, resilient, and globally competitive higher education ecosystem. Thus, the transformation of technology-based quality policies not only strengthens institutional governance but also serves as a national strategy to realize competitive, inclusive, and sustainable higher education in support of Indonesia’s Golden Vision 2045.